Activity of Moringa oleifera seed ethanolic extract against E. coli - Nurafifah, Diah Ayu; Widyastuti, Dyah Ayu; Minarti, Ipah Budi (Universitas PGRI Semarang, 2021)
Bacterial contamination in our environment is worrying, mainly contamination at drinking waters, vegetables, foods, soil which close to our daily activity. The main contamination in environment is caused by E. coli which simply found easily surround us. So, it leads to bigger problem if not immediately solve. One of possible yet safe compounds to overcome this problem is the use of natural product such as M. oleifera seeds as antibacterial agents. This study want to find out the ability of M. oleifera seed ethanolic extract as antibacterial agent against E. coli. Ethanolic extract of M. oleifera seeds are concentrated into 25%, 50%, and 75%, then treated to E. coli culture under laboratory condition. The inhibitory zone diameter which formed after 24 hours incubation was measured and compared to control with no extract treatment. The result of this study showed that there is inhibitory zone formed in three groups of treatmen (T1-T3), but there is no inhibitory zone formed at control group. The 75% ethanolic extract of M. oleifera seeds (T3) has the wides inhibitory zone diameter among four groups, followed by the 50% extract (T2) and 25% extract (T1) with diameter 15,03 ± 0,55 mm; 11,00 ± 1,32 mm; 7,03 ± 0,90 mm, respectively. All inhibitory zone diameter among groups in this research statistically different with strong inhibitory status at T2 as well as T3, and moderate inhibitory status at T1.